If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (8x + 9y)(8x + -9y) = 0 Multiply (8x + 9y) * (8x + -9y) (8x * (8x + -9y) + 9y * (8x + -9y)) = 0 ((8x * 8x + -9y * 8x) + 9y * (8x + -9y)) = 0 Reorder the terms: ((-72xy + 64x2) + 9y * (8x + -9y)) = 0 ((-72xy + 64x2) + 9y * (8x + -9y)) = 0 (-72xy + 64x2 + (8x * 9y + -9y * 9y)) = 0 (-72xy + 64x2 + (72xy + -81y2)) = 0 Reorder the terms: (-72xy + 72xy + 64x2 + -81y2) = 0 Combine like terms: -72xy + 72xy = 0 (0 + 64x2 + -81y2) = 0 (64x2 + -81y2) = 0 Solving 64x2 + -81y2 = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '81y2' to each side of the equation. 64x2 + -81y2 + 81y2 = 0 + 81y2 Combine like terms: -81y2 + 81y2 = 0 64x2 + 0 = 0 + 81y2 64x2 = 0 + 81y2 Remove the zero: 64x2 = 81y2 Divide each side by '64'. x2 = 1.265625y2 Simplifying x2 = 1.265625y2 Take the square root of each side: x = {-1.125y, 1.125y}
| x/2+3x/4=-9 | | 6d+7=19 | | 24w^6+24w^3=0 | | 11X-2=72 | | 5-p=20 | | 3=m-[-2] | | 6x+2(-4x-16)=-54 | | -64-25-9= | | 14=-7a | | xy-4y=21996 | | X=-3-13x | | 12000=.8(v)-.08(v)(6) | | (20x^2+23x-7)/x-1 | | (X-6)=-12 | | -9=15v/3 | | 1/2x+1+3/4=-9 | | -3(2x+5)=-27 | | 17-6xn=47+10xn | | 5*5=-45 | | 4x-6x+14x-21=0 | | 8-(5/x)=9-(10/x) | | d(3+c)= | | 69+p=96 | | 9x^2-90x+223=0 | | 12=4a | | 2x^2-9y+10=0 | | 3x+2x-17=8 | | 2=45pr | | 4x1/2 | | 24=-x-7x | | t-[-16]=9 | | 12-5r=-48 |